Cleavage plane after liquid‐bubble preparation of Descemet's membrane. Issue 6 (23rd December 2020) - Rickmann, Annekatrin; Wahl, Silke; Katsen‐Globa, Alisa; Schulz, André; Pütz, Norbert; Szurman, Peter
Abstract: Purpose: To investigate the ultrastructure of the cleavage plane of human cornea after liquid‐bubble‐prepared tissue for Descemet's membrane endothelial keratoplasty (DMEK). Methods: Experimental study with scanning electron microscopy (SEM) and block‐face SEM of 18 corneal specimens. Fresh human research donor corneoscleral discs ( n  = 12) were prepared with liquid‐bubble technique or examined as untreated controls ( n  = 3). In addition, Descemet's membrane samples, n  = 3, were obtained in DMEK surgery. Results: The cleavage plane after liquid‐bubble Descemet's membrane (DM) preparation was consistently located between interfacial matrix and posterior stromal collagen lamellae, providing a largely smooth surface exposing the amorphous interfacial zone without any significant amounts of adherent stromal remnants. No demarcation of a distinct pre‐DM layer could be detected. Conclusion: The DMEK graft preparation performed by liquid‐bubble technique showed a smooth cleavage plane and could not reveal any demarcation of a distinct pre‐DM layer.